Primary Outcomes of Accelerated Epithelium-Off Corneal Cross-Linking in Progressive Keratoconus in Children: A 1-Year Prospective Study - Sherif A. Eissa; Nashwa Badr Eldin; Ashraf Ahmed Nossair; Wael Ahmed Ewais (Journal of Ophthalmology)
Purpose. To evaluate corneal transparency following accelerated collagen cross-linking (ACXL) in pediatric keratoconus. Design. A prospective interventional case series. Methods. This study included 47 eyes (25 patients), aged 9–14 years, with documented progressive keratoconus. After applying 0.1% riboflavin drops, ACXL was performed. Assessment included corrected distance visual acuity (CDVA), uncorrected visual acuity (UCVA), corneal haze, and corneal densitometry in grayscale units (GSU). Result. The mean baseline and corneal densitometry peaked at 3 months post-ACXL while central and posterior densitometry showed a statistically significant increase (P<0.05) and peaked at 8 months postoperatively. By 12 months, densitometry in all corneal layers (P≥0.99) and concentric zones (P≥0.97) reached near baseline values. Slit-lamp graded haze peaked at 1 month to 1.82 ± 0.65 (P<0.05) and declined to near baseline at 12 months (0.39 ± 0.58). There was a statistically significant increase in the mean UCVA and CDVA at 12 months. Conclusion. Total and anterior corneal densitometry peaked after 3 months, while central and posterior densitometry peaked after 8 months. Maximum haze was at 1 month post-ACXL. All corneal layers, concentric zone densitometry and haze reached near baseline values after 1 year. Scheimpflug densitometry showed weak correlation with CDVA over the 12-month follow-up period (r=−0.193).